2023
DOI: 10.1186/s12888-023-04789-7
|View full text |Cite
|
Sign up to set email alerts
|

Do mindfulness-based interventions change brain function in people with substance dependence? A systematic review of the fMRI evidence

Abstract: Background Substance use disorders (SUDs) affect ~ 35 million people globally and are associated with strong cravings, stress, and brain alterations. Mindfulness-based interventions (MBIs) can mitigate the adverse psychosocial outcomes of SUDs, but the underlying neurobiology is unclear. Emerging findings were systematically synthesised from fMRI studies about MBI-associated changes in brain function in SUDs and their associations with mindfulness, drug quantity, and craving. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 72 publications
(180 reference statements)
0
2
0
Order By: Relevance
“…To measure the effects of mindfulness on cognitive and neuronal regulation of craving in addiction, neuroimaging methodologies such as functional magnetic resonance imaging (fMRI) can be employed. Studies have shown that mindfulness can modulate the neural circuitry associated with craving responses, indicating a potential for clinical significance [84]. Real-time fMRI provides a dynamic approach for evaluating the mindfulness-centered regulation of craving-related neural circuitry, offering direct measurements and feedback to guide mindfulness efforts.…”
Section: Impact On Cravingmentioning
confidence: 99%
“…To measure the effects of mindfulness on cognitive and neuronal regulation of craving in addiction, neuroimaging methodologies such as functional magnetic resonance imaging (fMRI) can be employed. Studies have shown that mindfulness can modulate the neural circuitry associated with craving responses, indicating a potential for clinical significance [84]. Real-time fMRI provides a dynamic approach for evaluating the mindfulness-centered regulation of craving-related neural circuitry, offering direct measurements and feedback to guide mindfulness efforts.…”
Section: Impact On Cravingmentioning
confidence: 99%
“…These changes were correlated with increased mindfulness, reduced medication use and diminished substance craving. [35] Vidrine JI et al conducted an investigation involving 158 patients who were tobacco cigarette smokers, having smoked at least 5 cigarettes per day for the past year and who were motivated to quit within the next 30 days. Their study provided preliminary evidence that the level of mindfulness among smokers seeking assistance to quit smoking is significantly associated with the level of withdrawal, agency and nicotine dependence -three factors recognized as crucial in predicting susceptibility to relapse.…”
Section: Maneesang W and Coworkers Conducted An Investigation About H...mentioning
confidence: 99%